2017
DOI: 10.1016/j.apjtm.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative application of combination of portal venous injection of donor spleen cells and intraperitoneal injection of rapamycin prolongs the survival of cardiac allografts in mice

Abstract: Preoperative application of combination of PVIDSC and rapamycin significantly prolonged the survival time of cardiac allografts in mice but not in mice pre-sensitized by skin grafting. This may be explained by the fact that combination of PVIDSC and rapamycin inhibited the cellular immune response and induced the expression of IL-10 from Tr1 cells and CD4CD25FoxP3 regulatory T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…50 Administration of rapamycin has been shown by many investigators to promote the expansion of CD4 + Treg but has been shown to be unable to inhibit the replication of memory T cells, even when combined with donor-specific transfusion (DST) in mice. 51 However, mammalian target of rapamycin (mTOR) inhibition via everolimus, in the context of costimulation blockade-resistant rejection that was nonresponsive to corticosteroids and ATG, was able to effectively inhibit the replication and effector function of CD8 + T EM cells. 52 These data suggest that mTOR inhibition as the sole immunosuppressive is not effective at inhibiting alloreactive memory responses, but it could be effective in combination with costimulation blockade as a rescue treatment for acute cellular rejection or even as maintenance immunosuppression.…”
Section: Use Of Steroids and Mammalian Target Of Rapamycin Inhibitorsmentioning
confidence: 99%
“…50 Administration of rapamycin has been shown by many investigators to promote the expansion of CD4 + Treg but has been shown to be unable to inhibit the replication of memory T cells, even when combined with donor-specific transfusion (DST) in mice. 51 However, mammalian target of rapamycin (mTOR) inhibition via everolimus, in the context of costimulation blockade-resistant rejection that was nonresponsive to corticosteroids and ATG, was able to effectively inhibit the replication and effector function of CD8 + T EM cells. 52 These data suggest that mTOR inhibition as the sole immunosuppressive is not effective at inhibiting alloreactive memory responses, but it could be effective in combination with costimulation blockade as a rescue treatment for acute cellular rejection or even as maintenance immunosuppression.…”
Section: Use Of Steroids and Mammalian Target Of Rapamycin Inhibitorsmentioning
confidence: 99%
“…Rapamycin has also shown its superiority over tacrolimus with respect to inhibiting B cell to plasma-cell differentiation [77]. In mice sensitized by prior skin graft, preoperative rapamycin increased the expression of regulatory T cells, but did not prolong the survival of mice after cardiac allotransplantation [78]. In donor skinsensitized mice, those with mTOR deletion in T cells had longer mean survival time (MST 19.5 days) versus wild-type recipients (MST 5.4 days) [75].…”
Section: Replacing Tacrolimusmentioning
confidence: 99%